Polsk akkusativ og dens norske ekvrvalenter - Kawczyńska, Elżbieta (Folia Scandinavica Posnaniensia, 2007)
In the article the author compares ways in which Polish and Norwegian mark the grammatical categories of direct and indirect object as well as different semantic types of adverbials. Having presented the sources and sketched the theoretical background the author goes on to discuss Norwegian equivalents of the Polish accusative within the above-mentioned categories.